The Roles of Malays in the Process of Islamization of the Malay World: A Preliminary Study - Mohd. Noh Abdul Jalil (International Journal of Nusantara Islam, 2014)
This paper will deal with problem concerning issues and theories of Islamization of the Malay world, with particular reference to the absence of the important element in these theories, which is the role and contribution of the Malay towards the process of Islamization in this region. Furthermore, there will be a discussion of the problem of generalization of existing theories, as well as issues concerning the limited amount of local evidence to support these theories. Sources for this analysis will be taken from studies of inscriptions, as well  as early Malay text, religious and non-religious texts. Comparison between the existing theories and direct and indirect evidence from sources will be used to ebolerate this matter. The ability of the early Malays to adopt and adapt foreign practices suggest that they also contributed to the entire process of Islamization of the Malay world one way or another.